Scale-Model Experiment on the Delayed Failure Mechanism of Deep Tunnels in Brittle Rock - Ning Zhang; Ziwei Chen (Applied Sciences)
Rock bursts usually happen during the hours or days after tunnel excavation, even in an unsupported opening where no collapses occur. To investigate the mechanism of those delayed failures in brittle rock tunnels, this paper showcases the performed scale-model test based upon the Jinping II headrace tunnelling project. The model test was conducted in a particularly designed loading apparatus; the scale-model is composed of a similar material for the deep brittle rock. The tunnel in the scale-model is excavated by a specially made drilling tool. The failure mode of the deep circle tunnel under isotropic and anisotropic geostress were obtained; the delay failure time was recorded, and the accompanying stresses and strains changing were monitored. Under isotropic geostress the failure shape has a smooth circle boundary, failure process totally costs 56 h. While under anisotropic geostress a dog-eared breakdown was found, the failure process amounted to 72 h. The time-to-failure was evaluated by delay failure theory, and the evaluation equation was implemented into in FEM code. Numerical simulations have been performed to simulate the failure time and failure mode. The numerical results of failure time and failure mode mainly match the scale-model testing results.